Implementation of the principle of Transparency Good Governance as an Effort to prevent & overcome Judicial Corruption in Judicial Institutions - Syauket, Amalia; Wirogioto, Ali Johardi (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Anyone who has ever dealt with a case in court will immediately feel and know that judicial corruption exists and is a reality that even tends to increase and become bolder. A series of empirical cases involving judges in the vortex of judicial corruption. Judicial corruption in judicial institutions to date has fundamentally and will continue to threaten the existence of law in society and the Indonesian rule of law because judges are one of the law enforcers. the purpose of this study is to analyze efforts to prevent and overcome juridical corruption. This research is included in a qualitative approach using secondary data. The results of the study state that efforts to prevent judicial corruption by judicial institutions are carried out by optimizing information technology in court administration which is the principle of transparency of good governance, while efforts to handle it through increasing the institutional capacity of the Judicial Commission strengthen by adding authority to the prevention aspect of supervision of judges' behavior through improving the system and organization within the judicial institution which is the principle of government effectiveness. The Judicial Commission is a watchdog institution that acts as a catalyst institutionally and organizationally.